Perception And Intention Of Adolescents Regarding Breastfeeding In Bangladesh - Shajeda Akhter; Tumpa Gharami; Halima Akter; Miftahul Falah; Fitri Nurlina; Heri Budiawan (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Perceptions and intentions about breastfeeding, especially among adolescents who represent future parents vary widely. Understanding these views is essential for designing impactful health education programs. This study aimed to assess perceptions and intentions toward breastfeeding among adolescents in Bangladesh. Method used a cross-sectional survey conducted on 132 adolescents aged 14-18 years from urban and rural areas of Bangladesh, who were selected through appropriate sampling. Data were collected using a structured questionnaire. Analysis was conducted using a computer program that used descriptive and inferential statistics. Significant relationships were identified between breastfeeding perception and several socio-demographic factors such as class level (t=2.107, p=.037), mother’s education level (t=2.215, p=.029), father’s education level (F=5.189, p=.007), and source of information on breastfeeding (F=4.290, p=.006). Additionally, a positive correlation was found between the number of siblings and breastfeeding perceptions (r=.047, p=.047). On the other hand, no significant relationship between a range of socio-demographic factors and adolescents' intentions regarding breastfeeding in Bangladesh was noticed in this study. P<.05 was used as the significant of this study. It is concluded that educational interventions that address both male and female adolescents, emphasizing the health benefits of breastfeeding and overcoming social barriers, are crucial for promoting a supportive breastfeeding culture.